The Role of the Indonesian Diaspora Network-Netherlands in Shaping the Transnational Social Space of the Indonesian Diaspora in the Netherlands - Bintang Corvi Diphda; Putri Alyaa Safira; Gertha Maria Gultom; Yoga Ramadhani; Angelique Kishiola Prima Foraihmbarasi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Indonesia’s long historical ties with the Netherlands have produced a diverse diaspora whose organizations shape cross-border relations, yet their concrete roles and mechanisms remain underexplored. This study asks how the Indonesian Diaspora Network-Netherlands (IDN-NL) helps form and sustain a transnational social space linking communities in the Netherlands with Indonesia. Using a library-based design, it analyzes documentary sources from 2013 to 2025, including organizational materials and secondary studies, to map actors, programs, events, and policy linkages. The findings show that IDN-NL coordinates thematic task forces in arts and culture, culinary, health, environment and sustainability, liveable cities, tourism, migrant workers, and My Roots. These units organize cultural-culinary events and community associations that enable regular interaction, support Indonesian business activity and remittances that reinforce economic ties, use digital platforms for routine coordination, and pursue advocacy on issues such as visa facilities and dual citizenship. Taken together, these activities integrate event-based nodes, online coordination, and policy support, transforming dispersed initiatives into a more organized and durable transnational social space. The article contributes an empirically grounded account of how a diaspora organization functions as an institutional connector, while indicating areas for improved documentation and capacity building in future research.